2019
DOI: 10.1016/j.proci.2018.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Edge flame propagation via parallel electric fields in nonpremixed coflow jets

Abstract: Recent investigations suggested that the primary influence of an electric field on a flame is flow modification caused by ionic wind, and that negative ions produced by the electron impact attachment should play a key role in the bi-directional ionic wind. In order to prove this hypothesis in electric fields parallel to the propagating flames, we designed a coflow experiment with laminar lifted flames in vertical electric fields produced by a nozzle and ground electrode installed over the flame.We found that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Through the action on the charged species in the flame, the external electric field will have a significant impact on the flow field in the combustion process, thus changing the combustion and electrical characteristics of the small flame. The flow near the flame will change when the electric field is applied 6 . The corresponding flow velocity, u , is defined as the ratio of flow velocity under external electric field to that without external electric field, u = u E / u E =0 , and u E =0 = 0.09 m/s.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the action on the charged species in the flame, the external electric field will have a significant impact on the flow field in the combustion process, thus changing the combustion and electrical characteristics of the small flame. The flow near the flame will change when the electric field is applied 6 . The corresponding flow velocity, u , is defined as the ratio of flow velocity under external electric field to that without external electric field, u = u E / u E =0 , and u E =0 = 0.09 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…The flow near the flame will change when the electric field is applied. 6 The corresponding flow velocity, u, is defined as the ratio of flow velocity under external electric field to that without external electric field, u = u E /u E=0 , and u E=0 = 0.09 m/s. The dashed line with squares in Figure 12 shows the corresponding flow velocity with various electric field strengths.…”
Section: The Effect Of Electric Field On Reactions and Flow Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ionic wind-driven flow-field modification was speculated to cause reduction in soot formation under a direct current (DC) electric field [1]; ionic wind-driven hydrodynamic instability and/or a modification of the transport property was hypothesized to lead to the faster burning character of outwardly propagating premixed flames under an alternating current (AC) electric field [6]; ionic wind improved flame stability in a numerical study of nonpremixed laminar jet flames under a DC field [11]; and, recently, bidirectional ionic wind blowing from a flame to both electrodes was observed in nonpremixed counterflow flames [16] followed by generalized visualization in premixed and nonpremixed jet flames with DC and AC fields [24], suggesting new understanding of the nature of ionic wind and its interaction with flames' structures. As a result of the insight of the bidirectional ionic wind, we proved that a propagation speed of a nonpremixed edge flame could be augmented [25], [26] or retarded [27] depending on a relative direction of electric field with respect to that of flame propagation. This implies that we should be able to actively control a propagating character of a flame using electric field.…”
Section: Introductionmentioning
confidence: 86%
“…This change makes the flame cells appear, which increases the flame surface area, promotes the mixing of fuel and oxidant, and increases fuel consumption and heat release per unit area. Yoon et al and Altendorfner et al applied an AC electric field in the original DC electric field research and used PIV and PLIF techniques to observe [11][12]. Experimental studies have shown that the addition of DC and AC reduces the speed of the flame upstream, resulting in an increase in the flame displacement speed.…”
Section: Bunsen Flame Methodsmentioning
confidence: 99%